Prevalence of zoonotic parasites in commercial fish species in the Alto Juruá, Brazil - Lima Araujo, Lilian Estefani (2023)
The family Raphidascarididae is composed of nematodes that carry out their life cycle in environments using diverse intermediate or paratenic hosts including invertebrates, fish, waterfowl, and mammals. The genera of this family include Raphidascaris Railliet & Henry, 1915, Ichthyascaris Wu, 1949 and Sprentascaris Petter & Cassone, 1984; all can act as fish parasites. The objective of this work was to analyze host fish of the family Loricariidae including two species of zoonoticnematodes. The study was carried out in the municipality of Cruzeiro do Sul, Acre, Brazil. A total of 42 Sprentascaris mahnerti Petter & Cassone, 1984 was collected from three hosts of the family Loricariidae, 27 from Limatulichthys griseus Eigenmann, 1909, 10 from Spatuloricaria sp. Schultz, 1944 and 5 in Hypoptopoma steindachneri Boulenger, 1895. For Raphidascaris sp. Railliet & Henry, 1915 a total of 12 larvae were found in five species of Loricariidae, where the highest value was found in Spataculoricaria sp. Schultz, 1944. The present study showed that Raphidascaris sp. parasitized a greater number of hosts than S. mahnerti, in which Spatuloricaria sp. was the host with the highest number of infected specimens. S. mahnerti showed the highest abundance of individuals, where the host with the highest number of infected specimens was L. griseus.